Provoking and Foreseeing Sudden Changes in the Workability of Pumped Concrete - Mortensvik Øystein; Thorstensen Rein Terje (Nordic Concrete Research)
It was attempted to provoke and foresee sudden loss of workability during concrete pumping through a series of full-scale tests. Batches of 2 m3 concrete were produced at a ready-mix plant, transported by concrete trucks and pumped by industrial pumps, to reveal sudden loss of workability. Different mix designs, extension hoses and pump setups were utilised in a six series experiment. An experimental procedure for measuring loss of workability at a laboratory scale was developed due to the standardised procedures for slump measurements camouflaging loss of workability. The experiments revealed that pumping through a boom seems to have a positive effect by reducing probability of sudden loss of workability. Furthermore, the fine aggregate seems to have a strong influence on the phenomenon, especially in the range of 0.25 mm to 1 mm.